Cycles of Conflict, Centuries of Change : Crisis, Reform, and Revolution in Mexico - Tutino, John, 1947-; Reina, Leticia; Servín, Elisa, 1955- (Book collections on Project MUSE., 2007)
Anthology about three of the persistent crises that have wracked Mexican society throughout its modern history, asking why these ruptures occurred, why they mobilized Mexicans of all social classes, and why some led to significant political transformatio.